Sedimentological characteristics of the coal-bearing Eocene deposits at the north of Suluova (Amasya) - Koç, Calibe; Türkmen, Ibrahim (My University, 2002)
The sedimentologic characteristics of coal-bearing Eocene deposits occuring at the north of Suluova (Amasya) have been examined in this study. The Eocene sedimentary sequence, resting uncomformably on the Upper Cretaceous Do?du Formation, comprises of the Çeltek Formation, the Armutlu Formation and the Osmano?lu Formation. It is uncomformably overlain by the Pliocene deposits. Nine facies and six facies association were identified in the Çeltek and Armutlu formations. These facies are ; bedded conglomerates (F1), thick bedded sandstones (F2), parallel laminated sandstone (F3), large cross-bedded sandstone (F4), wavy bedded sandstones (F5), grey-green mudstones (F6), red mudstones (F7), organic rich grey mudstones (F8) and coal (F9). Delta plain facies association comprises of F1, F2, F8 and F9 facies; delta front deposits, of F2 and F6 facies; lagoon facies association, of F2, F6 and F9 facies: shoreface sediments, of F4 and F6; offshore-transition deposits, of an alternation of F3, F5, F6 and F7 facies; offshore facies association, of F3 and F6 facies. The coal of the Çeltek Formation and Armutlu Formation were deposited in ponds and swamps of a delta plain and in a lagoon, respectively.
Suluova (Amasya) kuzeyindeki kömürlü Eosen çökellerinin sedimantolojik özellikleri
Keywords: Amasya; Coal; Delta; Lithofacies; Shallow marine